Attitudes toward fashion influencers as a mediator of purchase intention - Magano, José (2022)
Fashion influencers are a new phenomenon and profession to which many young individuals may currently aspire; such is its impact in the digital and online world. Hence, the article serves an upcoming group of fashion-influencers-to-be, as well as firms that seek the help of such professionals. This study aimed to test the mediating role of the attitude toward influencers in the relation between, on the one hand, perceived credibility, trustworthiness, perceived expertise, likeability, similarity, familiarity, and attractiveness, and, on the other hand, purchase intention. Path analysis was used to test a conceptual model in which attitude toward influencers mediates the relation between perceived credibility, trustworthiness, perceived expertise, likeability, similarity, familiarity, attractiveness, and purchase intention. Among the seven components, the association between perceived credibility, trustworthiness, perceived expertise, similarity, and familiarity, on the one hand, and purchase intention, on the other, was completely and significantly mediated through attitudes toward influencers. It was found that the attitude toward the influencer determines the purchase intent; this attitude is, in turn, conditioned by the competence, the resemblance, and the proximity that the consumer perceives in the influencer. Thus, to lead the consumer to buy a certain product, influencers must pay attention to perceived credibility, trustworthiness, perceived expertise, similarity, and familiarity with the product (or service).